PREVENTION OF LABOR DISPUTES AT THE LEVEL OF APPLICATION OF ACCOUNTING TOOLS AND CONTROL OF THE TAXATION PROCESS (EUROPEAN AND ASIAN LAW REVIEW, 2025)
The article presents an analysis of the problems and approaches to their solution in termsof the taxation process, control work of tax authorities in establishing the fact of substitution of labor relations with civil law that are combined organically with legal technique of an instrumental and operational nature. For this purpose, the labor and tax codes of the Republic of Belarus and the Russian Federation, judicial practice were analyzed. The main research methods were a systemic and comprehensive analysis of sources of legal regulation and comparative law. Individual methods are proposed for overcoming the identified contradictions that in the future will ensure appropriate forms for protecting the rights and legitimate interests of employees. This approach fits logically into the judgment on the need to consolidate at the level of the Constitutional Court definition and the Supreme Court Plenum resolution.
Keywords: legal technique; standard of good faith behavior; inspection; check; income tax; retraining; labor dispute commission